Welfare Effects of Social Cash Transfer Programs: Evidence from Egypt's Takaful and Karamah Programs - Hind Ibrahim Hanafy Mohammad (ZBW – Leibniz Information Centre for Economics, 2025)
Social cash transfers (SCTs) are considered a priority in least-developed countries, where the gap between the need for basic social protection and existing provisions is greatest. This study represents one of the first comprehensive impact evaluation treatments for Takaful and Karamah social cash transfer programs in Egypt. The results, based on propensity score matching (PSM) and odds-weighted regression, and data from the HIECS 2017-2018, confirm positive SCTs effects on per capita non-food consumption expenditures including healthcare and education for beneficiary households. The results also indicate threshold effects with SCTs mostly impacting healthcare expenditure among asset-poorer beneficiary households and education expenditure among asset-wealthier beneficiaries.
Keywords: I38; O2; D63; 330; Social cash transfers; impact evaluation; consumption expenditure; propensity score matching; odds-weighted regression